Applications of Solid-Phase Microextraction and Gas Chromatography/Mass Spectrometry (SPME-GC/MS) in the Study of Grape and Wine Volatile Compounds - Panighel, Annarita (Molecules, 2014)
Volatile compounds are responsible for the wine “bouquet”, which is perceived by sniffing the headspace of a glass, and of the aroma component (palate-aroma) of the overall flavor, which is perceived on drinking. Grape aroma compounds are transferred to the wine and undergo minimal alteration during fermentation (e.g., monoterpenes and methoxypyrazines); others are precursors of aroma compounds which form in winemaking and during wine aging (e.g., glycosidically-bound volatile compounds and C(13)-norisoprenoids). Headspace solid phase microextraction (HS-SPME) is a fast and simple technique which was developed for analysis of volatile compounds. This review describes some SPME methods coupled with gas chromatography/mass spectrometry (GC/MS) used to study the grape and wine volatiles.